(untitled) - Leigh, Ian (Oxford, 2000)
Leigh considers the competing and legally interlocking claims of local representative democracy, financial accountability and consumerism, and their implications for the governing structures of local authorities and for local electors, councillors, taxpayers, the users of local services, and council employees.
Keywords: Local government,Law; Law and legislation,Political aspects; Great britain